THE GEODYNAMIC EVOLUTION OF THE SOUTHERN EUROPEAN VARISCIDES: CONSTRAINTS FROM THE U/PB GEOCHRONOLOGY AND GEOCHEMISTRY OF THE LOWER PALAEOZOIC MAGMATIC-SEDIMENTARY SEQUENCES OF SARDINIA (ITALY) - Giacomini F.; Bomparola R.M.; Ghezzo C.; Guldbransen H. (My University, 2006)
The high-grade metamorphic complex of northern Sardinia consists of a strongly deformed sequence of migmatitic ortho- and paragneisses interlayered with minor amphibolites preserving relic eclogite parageneses. The protolith ages and geochemical characteristics of selected gneiss samples were determined, providing new constraints for reconstructing the Palaeozoic geodynamic evolution of this sector of the Variscan chain. The orthogneisses are metaluminous to peraluminous calcalkaline granitoids with crustal Sr and Nd isotopic signatures. One orthogneiss from the high-grade zone and one metavolcanite from the volcanic belt in southern Sardinia were dated by LAM-ICPMS (and SHRIMP) zircon geochronology. The inferred emplacement ages of the two samples are 469 ± 3.7 and 464 ± 1 Ma, respectively. The analysed paragneisses are mainly metawackes with subordinate metapelites and rare metamarls. Three paragneiss samples were dated: zircon ages scatter between 3 Ga and about 320 Ma, with a first main cluster from 480 to 450 Ma, and a second one from about 650 to 550. Variscan zircon ages are rare and mostly limited to thin rims and overgrowths on older grains. These data indicate that the high-grade complex principally consists of middle Ordovician orthogneisses associated with a thick metasedimentary sequence characterised by a maximum age of deposition between 480 and 450 Ma. The association of nearly coeval felsic-mafic magmatic rocks with immature siliciclastic sedimentary sequences points to a back-arc setting in the north Gondwana margin during the Early Palaeozoic. The Variscan metamorphic evolution recorded by the high-grade gneisses (Ky-bearing felsic gneisses and mafic eclogites) testifies to the transformation of the Late Ordovician–Devonian passive continental margin into an active margin in the Devonian–Early Carboniferous.
Keywords: ZIRCON; ORDOVICIAN; KYANITE; OSCILLATORY ZONING; ZIRCON POPULATION; Палеозой::Ордовикская; Paleozoic::Ordovician